MANAJEMEN PENGEMBANGAN SUMBER DAYA SANTRI BERBASIS TEKNOLOGI TEPAT GUNA DI PONDOK PESANTREN (PERSPEKTIF DAKWAH) - Dedy Susanto (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2017)
Strategic and systematic da'wah management for da'wah activities make Islam will experience a development. In case one of the da'wah institutions that require established management is a pesantren. Pesantren is one of the pillars of the Islamic struggle that has contributed greatly to religion as well as state. Hadi Mulya mentions pesantren as a cultural institution to develop a culture that has its own characteristics but also open itself to outside influences (Mulya, 1985: 99). The author conducts qualitative descriptive research. The process of searching data through three steps of data collection is through (1) observation to a number of related events and objects, (2) documentation related activities at Pondok Pesantren Robbi Rodliyya Semarang, (3) interviews with key personalities. The results showed that First, the implementation of boarding school management Robbi Rodliyya Banjardowo District Genuk Semarang City in the field of appropriate technology by planning, organizing, mobilizing and supervising the development of resources santri is good enough and professional. Second, the development of technology developed by Pondok Pesantren Robbi Rodliyya Banjardowo District Genuk Kota Semarang is a technology of electrical engineering and multimedia technology. isya 'and the community well.